PENGARUH FAKTOR KEUANGAN TERHADAP KEPUTUSAN PELAPORAN KEUANGAN DAN PELAPORAN PAJAK - Wahidatul Husnaini; Susi Retna Cahyaningtyas; Lukman Effendy (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2016)
This study emphasizes on one of the management strategies, by accessing whether a company would have a propensity toward the financial reporting or tax reporting. In addition, the study also aims to examine the various factors of corporate finance activities as a source of differences in weighing the financial reporting or tax reporting. These variables are short-term debt, long-term debt, cash deficits and the ability to access capital markets. This study focused on manufacturing companies listed in Indonesia Stock Exchange during 2012 - 2014. Sample was determined based on the purposive sampling method and as a result, this study obtained 66 units of observations. Hypothesis testing based on logit regression showed that (1) 51.5% of companies choose financial reporting above tax reporting while 48.5% chose tax reporting above financial reporting. (2) Long-term debt has negative influence on decisions of financial reporting or tax reporting. Companies with high long-term ratio tend to make aggressive tax reporting for interest expense is deductible expense. (3) Three independent variables such as short-term debt, financing deficit and access to capital markets has no influence the decision of financial reporting or tax reporting. Keywords: short-term debt, long-term debt, financing deficit, access to capital markets, reporting decision.